The Simplest, Isolable, Alkynyl Isocyanate HC≡CNCO: Synthesis and Characterization. Issue 48 (15th October 2019) - Qin, Yuanyuan; Lu, Bo; Rauhut, Guntram; Hagedorn, Manfred; Banert, Klaus; Song, Chao; Chu, Xianxu; Wang, Lina; Zeng, Xiaoqing
Abstract: Alkynyl isocyanates have been postulated as highly reactive intermediates in synthetic chemistry. Herein, the parent molecule HC≡CNCO is isolated for the first time. In sharp contrast to the previously reported short lifetime (ca. 15 s) at room temperature, we found that HC≡CNCO has a lifetime of 55 h in the gas phase (2 mbar, 300 K) with a melting point of −79.5 °C and vaporization enthalpy (Δ H vap ) of 23.1(1) kJ mol −1 . Apart from the IR (gas, solid, and matrix), 1 H and 13 C NMR, and UV/Vis spectroscopic characterization, its photoisomerization with a acylnitrene HC≡CC(O)N and cyanoketene NCC(H)CO has been observed. Abstract : The simplest alkynyl isocyanate, namely HC≡CNCO, has been successfully isolated as a neat substance. In sharp contrast to the previous described instability, HC≡CNCO is stable enough at room temperature for characterization with IR, UV/Vis, and NMR spectroscopy.